2022
DOI: 10.2147/prbm.s353778
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Academic Stress and Depressive Symptoms Mediated by Anxiety Symptoms and Hopelessness Among Chinese College Students

Abstract: Purpose Explore the potential mediating effects of anxiety symptoms and hopelessness on the relationship between academic stress and depressive symptoms among Chinese college students. Patients and Methods A total of 1309 college students with informed consent were recruited from a local university in China. Academic stress, anxiety symptoms, hopelessness, and depressive symptoms were assessed by self-report scales. Haye’s PROCESS macro for SPSS was used to test the hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 49 publications
2
28
0
1
Order By: Relevance
“…Academic anxiety refers to uneasy or unpleasant psychological reflection produced by the learning process, often caused by internal conflict, and is a state of tension specific to students ( Pekrun, 2005 ). Many studies have shown that learning stress is one of the most important reasons for academic anxiety among college students ( Leung et al, 2010 ; Tholen et al, 2022 ; Zhang et al, 2022 ). For example, Zhang et al (2022) found that English-learning stress was significantly positively associated with anxiety symptoms in a sample of 1,309 Chinese college students.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Academic anxiety refers to uneasy or unpleasant psychological reflection produced by the learning process, often caused by internal conflict, and is a state of tension specific to students ( Pekrun, 2005 ). Many studies have shown that learning stress is one of the most important reasons for academic anxiety among college students ( Leung et al, 2010 ; Tholen et al, 2022 ; Zhang et al, 2022 ). For example, Zhang et al (2022) found that English-learning stress was significantly positively associated with anxiety symptoms in a sample of 1,309 Chinese college students.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that learning stress is one of the most important reasons for academic anxiety among college students ( Leung et al, 2010 ; Tholen et al, 2022 ; Zhang et al, 2022 ). For example, Zhang et al (2022) found that English-learning stress was significantly positively associated with anxiety symptoms in a sample of 1,309 Chinese college students.…”
Section: Introductionmentioning
confidence: 99%
“…The results are also consistent with previous studies [ 18 , 22 ]. Undergraduate students with higher English learning stress had a lower level of English learning adaptability, and they were more likely to experience frustration, despair, and hopelessness [ 14 ]. These feelings may contribute to decreased self-efficacy in learning English, leading students to believe that they cannot complete learning tasks [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Undergraduate students with heavier perceived English learning stress could suffer from impaired learning self-efficacy. Chronic learning stress often leads to chronic negative effects such as anxiety, depression, and hopelessness [ 14 ]. Furthermore, excessive academic tasks as well as frequent academic failures and inadequacies can also damage undergraduate students’ learning motivation [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization defines academic stress as “the perception by certain students of events in the learning process as a threat to themselves, resulting in a range of undesirable behaviors” (e.g., worry, anxiety, or fear). It has been demonstrated that persistent learning stress can cause symptoms and issues such as low energy, depression, trouble concentrating, irritation, stress, and physical discomfort [ 6 ]. According to a poll of 27,343 college students who were under academic stress, 23% of college students reported feeling very stressed out and 91% reported having bad academic things happen to them in the previous 6 months [ 7 ].…”
Section: Introductionmentioning
confidence: 99%